1977
DOI: 10.1111/j.1600-0722.1977.tb00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of various microorganisms to chlorhexidine

Abstract: – The susceptibility to chlorhexidine of bacteria in aerobic, facultatively anaerobic and anaerobic isolates from clinical specimens of wounds, urine, saliva, and dental plaque was studied. Agar diffusion tests using 50 μg chlorhexidine discs and agar dilution tests were performed and the MIC values correlated with inhibition zone diameters, Anaerobic plaque strains were isolated and tested by the agar dilution method in an anaerobic glove box. Regression lines obtained for five agar media demonstrated a good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
151
0
17

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 13 publications
15
151
0
17
Order By: Relevance
“…According to Palmer et al 5 ., GICs have the potential of slowly releasing active agents, such as fluoride 24 , and the CHX incorporated into GICS can be similarly released into the oral cavity. This association is aimed at reducing severity and frequency of secondary caries by decreasing failures and unsuccessful use of these restorative materials 6,7,12,25 . Based on the observation of the presence of viable bacteria in the remaining dentin after removal of the infected layer and proper sealing of the cavity researchers observed that under in vitro conditions the addition of CHX to the GIC showed favorable antibacterial effect against microorganisms such as Streptococcus mutans, Lactobacillus spp., Candida albicans and Actinomyces naeslundii, acts on the biofilm act on the biofilm, which begins to show less pathogenic composition compared to acidogenic biofilm with a predominance of S. mutans, which would be formed without the presence of the antibacterial agent 3,9,[11][12][13][14]23,25 Türkün et al 3 demonstrated that GIC and CHX at a concentration of 0.5% have a long-term antibacterial effect without compromising the physical properties of the restorative material.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Palmer et al 5 ., GICs have the potential of slowly releasing active agents, such as fluoride 24 , and the CHX incorporated into GICS can be similarly released into the oral cavity. This association is aimed at reducing severity and frequency of secondary caries by decreasing failures and unsuccessful use of these restorative materials 6,7,12,25 . Based on the observation of the presence of viable bacteria in the remaining dentin after removal of the infected layer and proper sealing of the cavity researchers observed that under in vitro conditions the addition of CHX to the GIC showed favorable antibacterial effect against microorganisms such as Streptococcus mutans, Lactobacillus spp., Candida albicans and Actinomyces naeslundii, acts on the biofilm act on the biofilm, which begins to show less pathogenic composition compared to acidogenic biofilm with a predominance of S. mutans, which would be formed without the presence of the antibacterial agent 3,9,[11][12][13][14]23,25 Türkün et al 3 demonstrated that GIC and CHX at a concentration of 0.5% have a long-term antibacterial effect without compromising the physical properties of the restorative material.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the incorporation of antibacterial agents into restorative materials can result in changes in their physical properties depending the concentration used 3,5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10] CHX has been shown to be the most suitable agent in reducing ms due to its increased susceptibility when compared to other oral microorganisms. 11 Since CHX is retained in oral structures from which it is slowly released, this is one reason that its antibacterial effect is significantly longer than other agents. 6,12 The antibacterial effect of CHX is concentrationdependent.…”
Section: Introductionmentioning
confidence: 99%